Cloning and expression study of sugarcane (Saccharum sp.) sucrose transporter gene (SoSUT4) - Miftahudin; Rani Nur Fitriani; Dwi Andreas Santosa (Menara Perkebunan, 2024)
Sugarcane (Saccharum sp.) is a vital commodity for global sugar production and biomass generation, with sucrose being the primary sugar accumulated predominantly in the stem. The sucrose transporter protein is essential in facilitating sucrose transport across cells and over long distances within plants, from source to sink tissues. This study focused on the cloning and expression analysis of the SoSUT4 gene in the Bululawang sugarcane variety. A partial coding sequence of SoSUT4, comprising 802 nucleotides and encoding a 267-amino acid protein, was successfully cloned and sequenced. Sequence analysis revealed that the SoSUT4 protein shares high similarity with other SUT4 proteins in monocotyledonous plants, particularly with Saccharum spontaneum and Saccharum hybrid. Bioinformatics predictions indicated that the SoSUT4 protein is localized to the plasma membrane and contains six transmembrane helices. Gene expression analysis further demonstrated that SoSUT4 expression was significantly higher in the middle internodes of the stem compared to the youngest midsection of the leaves. This expression pattern correlates with higher sucrose accumulation in the stem, as reflected by elevated Brix levels in the stem (19.61%) compared to the leaves (19.48%). This finding suggests that SoSUT4 is essential for sucrose translocation to the stem, which serves as the primary storage site for sugar. The study provides valuable insights into the SoSUT gene family in sugarcane, particularly highlighting the role of SoSUT4 in sugar transport and accumulation. Future research should further investigate the underlying mechanisms of SoSUT4 and related genes to enhance our understanding of their impact on sugarcane yield, with potential applications for genetic engineering aimed at improving crop productivity. [Keywords: brix, relative expression, SoSUT4]